Multiparametric MRI analysis for the evaluation of MR‐guided high intensity focused ultrasound tumor treatment. (21st July 2015) - Hectors, Stefanie J. C. G.; Jacobs, Igor; Heijman, Edwin; Keupp, Jochen; Berben, Monique; Strijkers, Gustav J.; Grüll, Holger; Nicolay, Klaas
<x xml:space="preserve">Abstract</x> For the clinical application of high intensity focused ultrasound (HIFU) for thermal ablation of malignant tumors, accurate treatment evaluation is of key importance. In this study, we have employed a multiparametric MRI protocol, consisting of quantitative T1, T2, ADC, amide proton transfer (APT), T1ρ and DCE‐MRI measurements, to evaluate MR‐guided HIFU treatment of subcutaneous tumors in rats. K‐means clustering using all different combinations of the endogenous contrast MRI parameters (feature vectors) was performed to segment the multiparametric data into tissue populations with similar MR parameter values. The optimal feature vector for identification of the extent of non‐viable tumor tissue after HIFU treatment was determined by quantitative comparison between clustering‐derived and histology‐derived non‐viable tumor fractions. The highest one‐to‐one correspondence between these clustering‐based and histology‐based non‐viable tumor fractions was observed for the feature vector ADC, APT‐weighted signal (R2 to line of identity (R2y=x) = 0.92) and the strongest agreement was seen 3 days after HIFU (R2y=x = 0.97). To compare the multiparametric MRI analysis results with conventional HIFU monitoring and evaluation methods, the histology‐derived non‐viable tumor fractions were also quantitatively compared with non‐perfused tumor fractions (derived from the level of contrast enhancement in the DCE‐MRI measurements) and 240 CEM tumor fractions (i.e. thermal dose > 240 cumulative equivalent minutes at 43 °C). The correlation between histology‐derived non‐viable tumor fractions directly after HIFU and the 240 CEM fractions was high, but not significant. The non‐perfused fractions overestimated the extent of non‐viable tumor tissue directly after HIFU, whereas an underestimation was observed 3 days after HIFU. In conclusion, we have shown that a multiparametric MR analysis, especially based on the ADC and the APT‐weighted signal, can potentially be used to determine the extent of non‐viable tumor tissue 3 days after HIFU treatment. We expect that this method can be incorporated in the current clinical workflow of MR–HIFU ablation therapies. Copyright © 2015 John Wiley & Sons, Ltd.